Incorporating rocky desertification characteristic into soil erosion modeling in karst regions aligns better with regional conditions - Li, Rui; Xiao, Linlv; Cai, Feiyang; Gao, Jiayong; He, Maolin; Jing, Jun (International Soil and Water Conservation Research, 2025)
The Revised Universal Soil Loss Equation (RUSLE) is the most widely used soil erosion modeling method worldwide. The karst regions, influenced by geological conditions and human activities, feature extensive exposure of carbonate rocks on the surface, which presents challenges for the application of the RUSLE model in these areas. This study introduces the rocky desertification factor (D) to characterize the influence of exposed surface rock on soil loss. The relationship between rock exposure rate and soil erosion was incorporated into the RUSLE model to develop a RUSLE-D model. We compared the performance of the RUSLE and RUSLE-D models using long-term high-frequency hydrological signals from two typical karst catchments to validate the applicability of the RUSLE-D model in karst areas. The results indicated that under natural rainfall conditions, soil erosion decreased as the rock exposure rate increased, showing a negative exponential relationship. The RUSLE-D model estimated the multi-year average soil erosion rates for the SBT and GC catchments to be 8.99 and 14.63 t ha−2·yr−1, respectively. The R2 values for the RUSLE and RUSLE-D models in the SBT catchment were 0.34 and 0.78, respectively, with NSE values of −0.03 and 0.55, and PBIAS values of −81.39 % and 13.87 %; for the GC catchment, the R2 values were 0.14 and 0.68, with NSE values of −13.82 and 0.43, and PBIAS values of −182.85 % and −24.27 %. The MCI indices for the SBT and GC catchments were 0.56 and 0.96, respectively. The RUSLE-D model significantly improved the accuracy of soil erosion simulation in typical karst watersheds. This study underscores the importance of incorporating the rocky desertification factor in soil erosion assessments within karst areas. The newly developed RUSLE-D model contributes to further developing the USLE/RUSLE series of models, enhancing their applicability in karst areas.